CLINICAL EFFECTIVENESS OF INDIVIDUAL ADAPTIVE SPLINTS IN ORAL MUCOSAL REHABILITATION AND DENTURE RETENTION IMPROVEMENT IN COMPLETELY EDENTULOUS PATIENTS - Makhmud Khamidov (Modern American Journals, 2025)
Complete edentulism remains one of the most challenging conditions in prosthetic dentistry, often associated with impaired denture retention, prolonged adaptation periods, and pathological changes of the oral mucosa. The condition of the mucosal tissues of the denture-bearing area plays a decisive role in the stability and functional efficiency of removable complete dentures. Inadequate adaptation of the oral mucosa to prosthetic loading frequently leads to pain, inflammation, and reduced patient satisfaction.This article reviews and analyzes clinical and functional aspects of using individual adaptive splints as a preliminary stage of oral mucosal rehabilitation in completely edentulous patients. Special emphasis is placed on the mechanisms of mucosal adaptation, reduction of traumatic effects, and improvement of denture retention. The available evidence suggests that individual adaptive splints promote gradual functional adaptation of the mucosa, reduce pain symptoms, shorten the adaptation period, and enhance the clinical effectiveness of complete removable dentures.
Keywords: Complete edentulism, individual adaptive splints, oral mucosa, removable dentures, denture retention, prosthetic rehabilitation.